Giant Primary Epidural Extraskeletal Ewing Sarcoma in Cervical Spine in Infant Previously Evaluated for Neurodevelopmental Delay: Case Report and Review of the Literature - beiraghi toosi, mehran; Mousavi, Sousan; keykhosravi, ehsan; Rezaee, Hamid; Dehghanian, Paria; ebrahimzadeh, farnoosh; tavallayi, amin (Iranian Journal of Child Neurology, 2024)
Ewing sarcoma (ES) is a highly malignant tumor that originates from bones, especially long bones. ESarising from the epidural extramedullary space is highly unlikely, especially the cervical region. There have been only 6 cases of cervical epidural extraskeletal Ewing sarcoma (EEES) in children reported in the literature all of whom were older than 7-years-old. Out of 7 cases, including the one mentioned in this study, 4 were male (57%). Herein, we report a 1.5-year-old girl who presented with quadriparesis without cognitive impairment and had initially undergone metabolic disorder evaluation. The spine MRI revealed a mass in C2-T6 region and she underwent a biopsy of the tumor via laminectomy. Microscopic examination confirms a diagnosis of ES based on immunohistochemistry. This is the first literature that presents an infant with EEES.